Nitrogen addition changes the nitrogen conversion process in forest steppe ecotone by increasing enzyme activity - Baihui Ren; Haoyan Li; Daiyan Li; Meng Meng; Jiahuan Li; Long Bai; Yulong Feng (Ecological Processes)
Abstract Background The forest-steppe ecotone, a critical transition zone sensitive to global change, faces increasing nitrogen deposition. However, the interplay between nitrogen conversion processes and soil enzyme activity remains unclear. We investigated the effects of nitrogen addition on plant nutrient dynamics, microbial functional genes, and enzyme activity in northwest Liaoning, China. Results Nitrogen addition significantly increased leaf nitrogen content in Potentilla tanacetifolia (peak under N40) and Artemisia frigida (peak under N40), while Lespedeza daurica showed a non-linear response (peak under N20). Phosphorus content remained unaffected across species. Soil enzyme activities (urease, nitrate reductase, dehydrogenase) increased with nitrogen input, with protease activity rising proportionally to nitrogen addition rate. Functional genes (nirK, nifH, AOB-amoA) exhibited dynamic responses: nirK abundance peaked under N40, nifH under N10, and AOB-amoA increased with nitrogen input. Structural equation modeling revealed that nirK gene abundance positively influenced enzyme activity (λ = 0.512), while nifH negatively correlated with leaf N/P ratios (λ = −0.606). Soil protease activity directly drove leaf N/P ratios (λ = 0.734). Conclusions Nitrogen addition enhances plant nitrogen uptake and enzyme-driven mineralization, but species-specific responses highlight ecological trade-offs. Soil pH and protease activity are pivotal in mediating nitrogen conversion and plant nutrient stoichiometry. These findings underscore the need to integrate microbial and enzymatic dynamics into nutrient management strategies for ecotones under nitrogen enrichment.